Determinants of Financing Decisions for Micro Enterprises in Malang City in 2022-2023 Moderated by Islamic Financial Literacy - Fina Rosyada; Handoko, Azriel Rakaha; Riyanto, Feri Dwi; Andriani, Sri (Journal of Indonesian Applied Economics, 2024)
Purpose This study aims to analyze the Determinants of Financing Decisions in Micro Enterprises in Malang City Moderated by Sharia Financial Literacy Design/methodology/approach This research uses a mix method with purposive sampling techniques and the number of samples isas many as 60 respondents of micro business actors. The data of this study uses primary data obtained directly from the source using interview techniques, questionnaires, literature studies. Logistic regression is used to analyze the data. Findings This study revealed that variations in income and business age have a negative and significant effect on the variability of financing decisions. Meanwhile, guarantees have a positive and significant effect on the provision of financing decisions. Then, the variables of education, guarantees, and cultural characteristics do not affect the decision to provide financing. Vaiebel moderation itself is predicted to influence and strengthen the relationship between income variability and financing decisions. However, moderation variability has an influence and weakens the relationship between collateral variables and financing decisions. Research limitations/implications This research has limitations related to the amount of financing data conducted by Islamic banks Originality/value This study seeks to examine cultural characteristics with financing decisions which has rarely conducted before.